Physician Refusal or Withdrawal of Patient Treatment at Healthcare System of A University Hospital in Turkey (Journal of Basic and Applied Research in Biomedicine, 2022)
The refusal of the physician to give treatment to the patient is the end of relationship between the physician and the patient. The withdraw is end of relationship which has begun between the physician and the patient. The refuse or withdraw of the patient treatment, which constitutes a perception like the same act, causes significant ethical problems in the provision of health care. We carried out our research to identify physicians' considerations. We conducted a survey study between Research Assistants working in Clinical Departments in Inonu University Turgut Ozal Medical Center and in the treatment of patients. In study, 81 (80.2%) physicians were the most important factor in the refusal of the physician to give treatment to the patient, the patient or relative physical violence application. The reason for the refused was the patient who had psychological stress exerted 12 (11.9%), the medical difficulty was 7 (6.9%) and the patient 1 (1.0%) did not trust the physician's knowledge. It is possible to say that the main reason for the refusal of the patient treatment or withdraw treatment is the physician's injury of the honour.